FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN GEJALA CARPAL TUNNEL SYNDROME PADA KOMUNITAS OJEK ONLINE DI KOTA TANGERANG SELATAN TAHUN 2021 - Shafira Chairunnisa; Cornelis Novianus; Hidayati hidayati (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2021)
Background : Carpal Tunnel Syndrome (CTS) is a condition that causes numbness, pain, and tingle in the affectedindividual’s hands and arms. An online motorcycle driver is one of the high-risk jobs that can cause CTS because of along duration of work and repetitive movements. Increasingly long working duration will also cause repetitive motion,causing tissue interference around the carpal tunnel. Research Purpose : The purpose of the study is to learn about thefactors related to carpal tunnel syndrome’s symptomps of an online motorcycle driver community. Methodology : Thistype of research is a quantitative study with a design of cross sectional study. The population is 78 online motorcyclesdrivers, with samples are taken using a total samping technique of 78 people by data collection using a live questionnaire.Result : The results showed that there was a correlation between ages (p-value = 0.001), history of disease (p-value =0.002), personal protective equipment (p-value = 0,000), working period (p-value = 0,000), duration of work (p-value =0,031), repetitive movement (p-value = 0,000) with carpal tunnel syndrome and no correlation between obesity andcarpal tunnel syndrome (p-value = 0,735).Conclusion : There is correlation between carpal tunnel syndrome and ages,history of disease, personal protective equipment, working period, duration of work, and repetitive movement.